Where are we going? Postmodern thought and its influence on bioethical and biojuridic conflicts or dilemmas - Santome Sánchez, Aldo Alesandro (2021)
This article presents an analysis of some characteristics of postmodern thought, which have ended up influencing various bioethical and bio-legal dilemmas, such as abortion or euthanasia, among others. Thus, it is determined that many of the current positions, both in doctrine and in jurisprudence around these issues, have been the result of this current of thought, which, among other things, proposes the relativization of some fundamental rights, such as the life and freedom.